Investigação do mecanismo de formação de filmes porosos de TiO2 obtidos por anodização galvanostática - Sikora, Marina de Souza (2011)
In this work the experimental and theoretical aspects of the growth of titanium dioxide obtained by galvanostatic anodization were studied. The _lms were prepared by galvanostatic anodization of titanium, where the curve of voltage versus charge was investigated. In the initial growth there is an abrupt increase of the voltage, followed by a change in slope of the curve. In this region the voltage reaches a steady state characterized by oscillations around a mean value that are often associated with the phenomenon of _lm's breakdown, microdischarges (sparks) are also observed on the electrode surface. The experimental study began with the "system scanning" in which we used the factorial design in order to associate the experimental variables with the responses (electrochemical, morphological and microstructural). After this _rst study, we investigated the in_uence of applied charge on the system, keeping constant the other experimental conditions. In this investigation, we analyzed the in_uence of charge on the microstructure, morphology and also in the photoactivity of the _lms. The results revealed that the photoactivity in in- _uenced by both the microstructure and morphology. However, the microstructure seems more important for _lms obtained after the breakdown region, where the morphology remains constant. One possible explanation for these results is that the region of grain boundary acts as a recombination center of e=h+ pairs. In addition to these studies, the TiO2 doping was carried out with niobium. The physicochemical properties of the doped _lms were compared with pure _lms and it was observed that doping promotes an increase in the rate of crystallization of the _lms even when small amounts of dopants are introduced into the oxide. An applied study was conducted in order to apply the titanium anodization as a water heater system. The results of this investigation have shown that the titanium anodization provides greater e_ciency and heating rate when it is compared with comercial resistances. Finally, based on experimental results, we developed a model xxii for the growth of titanium oxide _lms prepared electrochemically. This semi-empirical model was developed from the "current burst model". The _rst stage consisted in the numerical simulation of the dissipation of the heat generated by a spark event in three ways (electrolyte, metal and oxide) using the _nite elements method. The simulation result have shown that the thermal dissipation extends over an area of up to 400 nm and the spark is able to fuse locally all the solid phases. Thus, the description of the oscillating system was made through its three main elements: the local oscillation mechanism (breakdown), desynchronization mechanism (dissolution) and lateral synchronization or interaction (promoted by the _ow of material).